Validasi dan kesesuaian konten situs Google sebagai media untuk mengintegrasikan gamifikasi dan teknologi terkini dengan pengamatan langsung dalam pendidikan biologi - Hery Fajeriadi; Aminuddin Prahatama Putra; Bunda Halang; Nurul Aulia; Gt. Muhammad Irhamna Husin; Muhammad Naufal Azzam; Muhammad Abdi Gusti; Fatimah Ghina Azzahra; Intan Sari; Siti Hafsoh; Rahmi Saputri; Hanisa Hanisa (Biosfer: Jurnal Pendidikan Biologi, 2026)
Biology education requires interactive digital media capable of supporting direct observation activities and student engagement. However, the application of gamification-based media integrated with field observations in biology education remains limited and is rarely evaluated in terms of its validity and practicality. This study aims to analyze the validity and practicality of a gamification-based Google Sites platform named “Eco-Quest” for observation-based biology learning. The study employed a Research and Development (R&D) approach using Tessmer’s formative evaluation model, which includes expert review and one-to-one evaluation stages. Study participants consisted of three expert validators and ten students. Data were collected via expert validation sheets and student response questionnaires, then analyzed descriptively using a 1–5 rating scale and percentage conversion. The expert validation results showed an average score of 3.37, categorized as valid, while the system test achieved an average score of 4.63, categorized as excellent. The study findings indicate that the integration of gamification features, visual navigation, and observation-based activities enhances student engagement, interaction, and the effectiveness of task management. The aspects students found most helpful were the gamification system and visual display, while the main challenge identified was internet connectivity. Therefore, the “Eco-Quest” platform is suitable for use in biology education and requires further development through improved accessibility and testing of learning outcomes.